ANALYZING MANADO YOUTH PREFERENCES ON ONLINE MOVIE STREAMING - Leticya Gala; Willem J. F. A. Tumbuan; Shinta Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Nowadays, young people dominate the use of the internet. One thing that we can do with the internet is watch a movie. Currently, there are many online movie streaming platforms available, including Viu, Disney+ Hotstar, and Netflix. Based on the problem's background, this research aims to determine which movie streaming platforms are most demanded by young people in Manado. This research uses quantitative methods to measure data. The method used is the Analytical Hierarchy Process (AHP) method. The AHP method is for rating alternatives to decisions and selecting the best multiple criteria, allowing users to assess the relative weights of some criteria given intuitively. The study shows that young people in Manado prefer the Disney+ Hotstar streaming application over other alternatives. Ease of Use is the essential criterion for young people in Manado in deciding which movie streaming application they choose.   Keywords: customer preferences, analytical hierarchy process